Exploration of self-medication practice in Pokhara valley of Nepal - Sabita Paudel; Bijay Aryal (BMC, 2020)
Abstract Background Self-medication (SM) is the practice of consuming medication without the consultation of physician. The drugs most commonly self-medicated are paracetamol, analgesics, ranitidine, oral rehydration solution and antibiotics. The objective of the study was to assess the SM status and its causes in Pokhara valley of Nepal. Method The study was conducted among the people residing in Pokhara metropolitan city. The study duration was of 4 months from April to July, 2018. The study population were patients attending health general and oral health screening programs at Baidam, Birauta, Hemja and Pame areas of Pokhara. Structured questionnaire was used to collect demographics of the patients and the details of the usage of self-medication. Result Out of 201 patients, 38.2% patients were found to be self-medicating. The most common illness sought for SM was ache (headache, body ache) in 50% subjects followed by cough and cold in 31% and gastritis in 23%. Paracetamol was the drug consumed by 16 subjects followed by nimesulide by 11. Lack of knowledge about the disadvantages of SM led to self-medication in 65% of respondents. The personnel most commonly consulted for medication were pharmacists (60%). Conclusion The trend of SM is high in Pokhara valley. The comedics were consulted most often for SM due to lack of knowledge of consultation to physicians. The public should be made aware about SM.